Study of the protection capacity of the ashes of bagasse from sugar cane, in relation to corrosion of armor under the action of chloride ions (Research, Society and Development, 2022)
The sugar and alcohol production plants in Brazil have been growing in recent years, using the burning of sugarcane bagasse to co-generate energy for their own consumption in various productive sectors and also for supply to third parties. In the country, sugarcane production is concentrated in the Center-South and North-Northeast regions. This activity contributes to the increasing amount of waste generated in the process, among them, the ash from the burning of sugarcane bagasse (SBA). This article aims to verify the feasibility of the SBA and its capacity for corrosion protection of armour under action of chloride ions, in partial replacement of Portland cement in concrete, dosed with a maximum of 0%, 5%, 10%, 15% and 25% of SBA, due to their pozzolanico potential. The methodology consisted in carrying out the tests of resistance to compression, absorption by capillarity, absorption by immersion, depth of carbonation and corrosion potential, aiming to analyze the mechanical properties and the aspects of durability. The results indicated the levels of 10% and 15%, as the best levels for the replacement of Portland cement by SBA. This replacement has not caused significant damage to the concrete’s resistance and reduced the rate of water absorption. On the other hand, only the levels of 0% and 5% had a low probability of corrosion. Therefore, it was concluded that the SBA can be used as a partial replacement of Portland cement in unreinforced concrete, fostering the sustainability in civil construction, in the sugar cane sector and in society.